Mothers' family support and mothers' work on the success of exclusive breastfeeding in 7-12 months old infants - Komalasari Komalasari; Hikmah Ifayanti; Feri Agustriyani (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Exclusive breastfeeding for six months is one of the effective interventions to reduce the Infant Mortality Rate (IMR). Based on data from the community health center of Penawar Jaya, infants who received exclusive breastfeeding in 2019 are still low at only 49%. The research objective was to determine the correlation between family support and mothers' work on the successful accomplishment of exclusive breastfeeding for infants aged 7-12 months in the work area of the community health center of Penawar Jaya, Tulang Bawang Regency 2021. This research type is an analytical survey method with a cross-sectional design. The population is all mothers in the work area of the community health center of Penawar Jaya, Tulang Bawang Regency, who have infants aged more than 7-12 months totaling 463 people, with a sample of 43 people, which is calculated using the minimum sample formula from Lemeshow. Univariate analysis of percentage and bivariate analysis using chi-square test. The research results on family support for mothers were 44.2%, and mothers worked 67.4%. There is a correlation between family support for the accomplishment of exclusive breastfeeding.   The p-value = 0.048, and there is a correlation between workers and the success of exclusive breastfeeding for mothers who have infants aged 7-12 months in the work area of the community health center of Penawar Jaya, Tulang Bawang Regency 2021 with p-value = 0.017 and OR 6.967. Suggestions for working mothers are expected to increase understanding regarding breastfeeding, and mothers can also involve all family members to play a role in breastfeeding. Abstrak: Pemberian ASI secara eksklusif selama 6 bulan terbukti merupakan salah satu intervensi efektif dapat menurunkan Angka Kematian Bayi (AKB). Berdasarkan data Puskesmas Penawar Jaya bayi yang mendapat ASI Eksklusif pada Tahun 2019, masih rendah yaitu hanya 49%. Tujuan penelitian ini diketahui hubungan antara dukungan keluarga dan pekerjaan ibu terhadap keberhasilan ASI eksklusif pada bayi usia 7-12 bulan di Wilayah Kerja Puskesmas Penawar Jaya Kabupaten Tulang Bawang Tahun 2021. Jenis penelitian ini metode Survey analitik dengan rancangan cross sectional. Populasinya adalah seluruh ibu di wilayah kerja UPTD Puskesmas Penawar Jaya Kabupaten Tulang Bawang yang mempunyai bayi berusia lebih dari 7-12 bulan berjumlah 463 orang, dengan sampel 43 orang, yang dihitung menggunakan rumus sampel minimal dari Lemeshow. Analisis univariat persentase dan analisis bivariate uji chi square Hasil penelitian dukungan keluarga pada ibu 44,2%, ibu Bekerja 67,4 %. Ada hubungan antara dukungan keluarga terhadap keberhasilan ASI eksklusif p value = 0,048dan ada hubungan antara pekerja terhadap keberhasilan ASI eksklusif pada ibu yang memiliki bayi usia 7-12 bulan di Wilayah Kerja Puskesmas Penawar Jaya Kabupaten Tulang Bawang Tahun 2021 p value = 0,017 dan OR 6,967. Saran bagi Ibu bekerja diharapkan dapat meningkatkan pemahaman berkaitan dengan penyimpanan dan pemberian ASI, dan ibu juga dapat mengikutsertakan semua anggota keluarga untuk berperan dalam pemberian ASI.